2022
DOI: 10.1097/md.0000000000028850
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative therapies for stable angina pectoris of coronary heart disease

Abstract: Background: Stable angina pectoris in patients with coronary heart disease is a clinical syndrome of rapid transient ischemia and hypoxia of myocardium due to the increase of myocardial load on the basis of fixed severe coronary artery stenosis. In recent years, the incidence rate of this disease has been rising steadily, which seriously threatens human life and health. When the disease occurs, its complementary and alternative therapy can relieve chest pain, improve cardiac function, and reduce adverse events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Among them, 1,027 were duplicates, and 657 were excluded after reading the title or abstract. Finally, 51 trials were reviewed at the full-text level for further evaluation, of which 12 were excluded (Reasons of excluding studies were provided in Supplementary Table S5), and the remaining 39 studies (Cui et al, 2008;Gao et al, 2009;Wang and Zhang, 2009;Chai, 2010;SUn, 2010;Zhong, 2010;Zhou, 2010;Zhuang and Wu, 2010;Gao and Feng, 2011;Sui, 2011;Zhang and Yu, 2011;Zhao and Liu, 2011;Ma and Xi, 2012;Meng et al, 2012;Xu, 2012;Zhang, 2012;Liu and Zhang, 2013;Yuan, 2013;Dai, 2014;He et al, 2014;Ren and Wang, 2014;Zhu, 2014;Li, 2015;Liu and Cheng, 2015;Wang, 2015;Chen et al, 2016;Wu, 2016;Zhang, 2016;Zhou, 2017;Liu, 2018;Zhang et al, 2018;Sun et al, 2019;Cai, 2021;He et al, 2022;Zhang, 2022) were included in the final review (Figure 1).…”
Section: Results Of Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, 1,027 were duplicates, and 657 were excluded after reading the title or abstract. Finally, 51 trials were reviewed at the full-text level for further evaluation, of which 12 were excluded (Reasons of excluding studies were provided in Supplementary Table S5), and the remaining 39 studies (Cui et al, 2008;Gao et al, 2009;Wang and Zhang, 2009;Chai, 2010;SUn, 2010;Zhong, 2010;Zhou, 2010;Zhuang and Wu, 2010;Gao and Feng, 2011;Sui, 2011;Zhang and Yu, 2011;Zhao and Liu, 2011;Ma and Xi, 2012;Meng et al, 2012;Xu, 2012;Zhang, 2012;Liu and Zhang, 2013;Yuan, 2013;Dai, 2014;He et al, 2014;Ren and Wang, 2014;Zhu, 2014;Li, 2015;Liu and Cheng, 2015;Wang, 2015;Chen et al, 2016;Wu, 2016;Zhang, 2016;Zhou, 2017;Liu, 2018;Zhang et al, 2018;Sun et al, 2019;Cai, 2021;He et al, 2022;Zhang, 2022) were included in the final review (Figure 1).…”
Section: Results Of Study Selectionmentioning
confidence: 99%
“…A total of 19 out of the included 39 studies reported adverse reactions. Of these, no adverse reactions were observed in eight studies (Danesh et al, 1998;Wang and Zhang, 2009;Zhou, 2010;Zhang and Yu, 2011;Zhao and Liu, 2011;Xu, 2012;Ren and Wang, 2014;He et al, 2022). Two studies (SUn, 2010;He et al, 2014) reported no adverse reactions in the experimental group, but adverse reactions such as facial flushing and the slightly increased of alanine aminotransferase (ALT) were observed in the control group.…”
Section: Adverse Reactionsmentioning
confidence: 98%
“…Among the 17 RCTs, 10 (17-26) were randomly assigned by the random number table method and rated as low risk, while the rest (27)(28)(29)(30)(31)(32)(33) did not describe the method of random sequence generation and were rated as unclear; only one (20) used double-blind and placebo controls, and the use of blindness and allocation hiding was rated as low risk, while the rest (17)(18)(19)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) did not mention the use of blindness and allocation hiding and were rated as unclear; none of the studies (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) reported outcome indicators with incomplete information, and none of them had a selective reporting; thus, their risk rating was evaluated as low. For other biases, all (17)(18)(19)(20)(21)…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…According to pathological anatomy and the observed pathophysiological changes, angina pectoris has a clinical phenotype of coronary heart disease, which is related to the atherosclerosis of coronary arteries causing luminal narrowing or occlusion. Moreover, an increase in myocardial load results in temporary ischaemia and myocardial hypoxia, which leads to the patient developing clinical manifestations such as chest tightness, chest pain, and shortness of breath [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%